Filler with multi-layer structure as well as preparation method and application of filler

By designing a filler with a multi-layer structure, including a low dielectric constant material layer, a hollow part and a resin layer, and adjusting the proportion of each layer so that the specific gravity of the filler is in the range of 0.4~1.5g/cm3, the existing technology is solved The problem of insufficient density of hollow silica particles is achieved, and the effect of low dielectric constant and low dielectric loss of the substrate is achieved.

CN119350888APending Publication Date: 2025-01-24ZHEJIANG THIRD AGE MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411484005.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to prepare surface-densified hollow silica particles, resulting in an increase in dielectric loss during high-frequency signal transmission and unable to meet the requirements of high dielectric performance.

Method used

Adopt a multi -layer -structured filler design, including the low -agent constant material layer, the lunar ministry and resin layer of the material layer formed by the material layer, by adjusting the proportion of each structure layer, the proportion of the filler is 0.4 ~ 1.5g/cm3 range range Inside, to achieve excellent decentralization and low -agent electricity performance.

Benefits of technology

It effectively reduces the dielectric constant and dielectric loss of the substrate, improves the dispersion and stability of the substrate, and meets the high-fidelity and low-latency requirements of high-frequency signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350888A_ABST
    Figure CN119350888A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fillers, and discloses a filler with a multilayer structure and a preparation method and application thereof. According to the filler with the multi-layer structure provided by the invention, the proportion of the hollow part, the low-dielectric-constant material layer and the resin layer is adjusted, so that the filler has a proportion suitable for that of a resin composition, the filler has excellent dispersity in the resin composition, and the filler plays a role in the low dielectric property of a prepared substrate. Furthermore, the filler has a low dielectric constant in a wide distribution range of 0.3-20 [mu] m in particle size, so that the fillers with different particle sizes play a grading role, and the dielectric property of the prepared substrate is further reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fillers, and in particular to a filler with a multi-layer structure and a preparation method and application thereof. Background Art

[0002] With the rapid development of the microelectronics industry, semiconductor chips are constantly developing towards high integration, miniaturization, high frequency, and high power, so higher requirements are also put forward for the dielectric properties of their electronic packaging materials. In the semiconductor field, when passive components, semiconductor components, electroacoustic devices, display devices, optical devices, and radio frequency devices are assembled into devices, circuit board substrate materials such as high-density interconnect boards, high-frequency high-speed boards, and motherboards are required. At this stage, there are requirements for substrate materials to reduce dielectric constants and dielectric losses. Generally speaking, substrates with low dielectric constants (Dk) and dielectric loss factors (Df) can better achieve high fidelity and low latency effects during high-frequency signal transmission.

[0003] In the prior art, in order to reduce the dielectric constant of the substrate, it is often achieved by reducing the dielectric constant of the substrate filler, such as the patent with application publication number CN109071239A, which discloses a method for manufacturing hollow silica particles. Because the dielectric constant of air is much smaller than the dielectric constant of silica, compared to solid silica, hollow silica can reduce the dielectric constant of the silica filler as a whole due to the presence of a hollow structure. The patent is prepared as a hollow structure by silica as a filler to achieve the effect of reducing the dielectric constant of the filler. However, in the prior art, it is difficult to prepare hollow silica particles with a completely dense surface. Most of them are mesoporous silica on the market, and due to the increase of pores on the surface of silica, it is easier to absorb moisture in the air, which will cause the dielectric loss to increase, and then although it brings the effect of reducing the dielectric constant due to the presence of a hollow structure, due to the water absorption problem, its overall dielectric loss will increase, which is not enough to meet the current high requirements of the field for dielectric properties. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a filler with a multilayer structure and a preparation method and application thereof.

[0005] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a filler having a multilayer structure, wherein the filler is a spherical particle, which includes a low dielectric constant material layer, a hollow portion surrounded by the low dielectric constant material layer, and a resin layer disposed on the outer surface of the low dielectric constant material layer; The space of the hollow part contains vacuum or gas, and the gas is selected from one or more of air and inert gas; The specific gravity of the filler is 0.4-1.5 g / cm 3 .

[0006] The filler with a multilayer structure of the present invention has a specific gravity suitable for the resin composition of 0.4-1.5 g / cm by adjusting the proportion of each structure of the hollow part, the low dielectric constant material layer and the resin layer. 3 , so that the filler has excellent dispersibility in the resin combination, and then the low dielectric properties of the obtained substrate are played a role. The material of the commonly used filler in the semiconductor field can be used as the making material of the low dielectric constant material layer of the filler of the present invention, so as to further reduce the dielectric constant and dielectric loss of the commonly used filler, and then the dielectric loss of the obtained substrate is reduced. The material of the commonly used filler in the semiconductor field has the characteristics of low dielectric constant.

[0007] The filler of the present invention has a multilayer structure, which makes the prepared substrate have an extremely low dielectric constant. The important thing is to adjust the proportion of each structural layer of the hollow part, the low dielectric constant material layer, and the resin layer. Therefore, the substrate is prepared under the same preparation conditions, and the filler is a filler with a multilayer structure of a hollow part, a low dielectric constant material layer, and a resin layer. If the specific gravity of the filler is 0.4-1.5g / cm 3 The dielectric constant of the substrate made of this filler is low. Although the dielectric constant of the air, vacuum or inert gas in the hollow part is lower than that of the low dielectric constant material layer and the resin layer, the dielectric constant of the filler as a whole can be reduced by increasing the volume proportion of the hollow part. However, if the specific gravity of the filler is not between 0.4 and 1.5 g / cm 3 In the range of 0.4-1.5 g / cm2, the dielectric constant of the substrate made of the filler is 0.4-1.5 g / cm2 compared with the above-mentioned specific gravity. 3 The dielectric constant of the substrate made with filler is higher.

[0008] In addition, since the resin layer is disposed on the outer surface of the low dielectric constant material layer, it is possible to prevent the resin composition components from being mixed into the low dielectric constant material layer during the subsequent process of mixing the filler with the resin composition to prepare the substrate, thereby preventing the dielectric constant of the low dielectric constant material layer from increasing. Therefore, when the substrate is prepared under the same preparation conditions and the specific gravity of the filler is the same appropriate specific gravity, the dielectric constant of the filler provided with the resin layer is lower than that of the substrate prepared without the filler.

[0009] In addition, due to the setting of the hollow part, the volume ratio of the hollow part can be adjusted as large as possible to take advantage of the low dielectric constant of air, vacuum or inert gas, and the overall specific gravity of the filler with a multilayer structure is 0.4~1.5g / cm 3The range of the dielectric constant of the substrate made of the filler is finally further reduced. The space of the hollow part contains vacuum, air or inert gas, which can be achieved by existing technology. For example, the hollow particles are directly prepared from the material forming the low dielectric constant material layer, and the hollow part and the low dielectric constant material layer can be directly integrated to form an inert gas. By further purging with inert gas, the space of the hollow part can contain inert gas.

[0010] Preferably, the specific gravity of the filler is 0.6-1.3 g / cm2 as measured by a true density meter based on an oxygen-based dry pycnometer. 3 .

[0011] Preferably, the volume of the hollow portion accounts for 33% to 95% of the total volume of the hollow portion and the low dielectric constant material layer.

[0012] The material forming the low dielectric constant material layer is often higher in dielectric constant than the resin layer material. However, the thermal expansion coefficient of the resin layer material is greater than that of the material forming the low dielectric constant material layer. When processing and preparing the substrate, there is an expansion difference. When the expansion difference is too large, there is a problem of peeling between the resin layer and the low dielectric constant material layer. The peeling of the resin layer will cause uneven dispersion of the filler and water absorption problems. Therefore, it is necessary to make the proportion of the resin layer smaller to reduce the expansion difference and avoid peeling of the resin layer. Therefore, in the filler of the present invention, on the premise of ensuring that the mass proportion of the resin material is reduced, the specific gravity of the filler is set at 0.4~1.5g / cm 3 , the dielectric constant of the filler can be made better (smaller). In the filler of the present invention, in order to reduce the amount of resin material used, the volume of the hollow part accounts for 33% to 95% of the total volume of the hollow part and the low dielectric constant material layer, which can make the dielectric constant of the filler with a multilayer structure smaller.

[0013] More preferably, the volume of the hollow portion accounts for 42% to 87% of the total volume of the hollow portion and the low dielectric constant material layer.

[0014] Preferably, under the condition of 1 GHz, the Dk of the material forming the resin layer is ≤3.

[0015] A resin material with a low dielectric constant Dk can make the dielectric constant of the prepared filler low, which ultimately helps to reduce the dielectric loss of the prepared substrate.

[0016] Preferably, the thickness of the resin layer does not exceed 1 / 4 of the diameter of the filler.

[0017] More preferably, the thickness of the resin layer does not exceed 300 nm.

[0018] Preferably, the average particle size of the filler is 0.3-20 μm.

[0019] Furthermore, the present invention can make the filler particle size have a wide distribution range of 0.3-20 μm, and has fillers with low dielectric constants within the wide particle size distribution range, giving play to the grading effect of fillers with different particle sizes, so that the dielectric properties of the prepared substrate are further reduced.

[0020] Preferably, between -60°C and 300°C, the thermal expansion coefficient of the material forming the low dielectric constant material layer is ≤20ppm / K.

[0021] By making the thermal expansion coefficient of the material forming the low dielectric constant material layer not exceed 20 ppm / K, the stability of the substrate can be improved, and the dielectric constant of the substrate can also be maintained at a low state after being placed for a period of time.

[0022] In a second aspect, the present invention provides a method for preparing a filler having a multilayer structure, comprising the following steps: Step S1: adding an organic resin into a first solvent to form a solution; Step S2: providing a hollow spherical particle, and dissolving the hollow spherical particle in a second solvent to form a dispersion; Step S3: mixing the dispersion with the solution to precipitate the organic resin and form a resin layer on the surface of the hollow spherical particles; Step S4: separating the solid and liquid of the mixed system obtained in step S3, and drying the solid to obtain a filler; The specific gravity of the filler is 0.4-1.5 g / cm2 as measured by a true density meter using a dry pycnometer based on oxygen. 3 .

[0023] Preferably, the hollow spherical particles have a hollow ratio of 33-95%.

[0024] Preferably, the thickness of the resin layer does not exceed 1 / 4 of the diameter of the filler.

[0025] Preferably, the organic resin is selected from one or more of polybutadiene, polystyrene butadiene copolymer, polyphenylene ether, cycloolefin copolymer, SI and SIS copolymer, ethylene propylene diene copolymer, polyphenylene ether-modified polystyrene butadiene rubber, polyphenylene ether-modified SI and SIS copolymer. Among them: SI polymer is a diblock copolymer composed of two monomers of styrene (S) and isoprene (I); SIS copolymer is a styrene-isoprene-styrene triblock copolymer.

[0026] Preferably, the first solvent can be selected from one or more non-polar solvents, such as toluene, xylene, etc.; the second solvent can be selected from one or more water, methanol, and ethanol solvents.

[0027] Preferably, the average particle size of the filler is 0.3-20 μm.

[0028] In a third aspect, taking silica filler as an example, the present invention provides a method for preparing a filler with a multilayer structure, comprising the following steps: (1) adding an organic resin into a first solvent to form a solution; (2) providing a hollow silica particle, and dissolving the hollow silica particle in a second solvent to form a dispersion; (3) mixing the dispersion with the solution to precipitate the organic resin and form a resin layer on the surface of the hollow silica particles; (4) separating the solid and liquid of the mixed system obtained in step (1), taking the solid and drying it to obtain a filler; The specific gravity of the filler is 0.4-1.5 g / cm2 as measured by a true density meter using a dry pycnometer based on oxygen. 3 .

[0029] Hollow silica powder is a commonly used filler in the semiconductor field. Due to its low true density, it is easy to have problems such as powder floating, uneven dispersion, and poor bonding ability when mixed with resin materials to make substrates, which leads to the substrate made of hollow silica powder being easy to absorb water, and ultimately increasing dielectric loss. How to reduce the dielectric loss of substrates made of hollow silica powder is a research focus in the semiconductor field.

[0030] In the preparation method provided by the present invention, a resin layer is formed on the surface of the hollow silica particles, and its specific gravity is 0.4-1.5 g / cm 3 Within the range of , the silica filler product and the resin material can be evenly mixed and dispersed, the density of the prepared substrate is improved, the water absorption problem is avoided, and the dielectric loss is reduced.

[0031] Preferably, the specific gravity of the filler is 0.6-1.3 g / cm2 as measured by a true density meter based on an oxygen-based dry pycnometer. 3 .

[0032] Preferably, the hollow silica particles have a hollow ratio of 33-95%; The thickness of the resin layer does not exceed 300 nm.

[0033] Preferably, the organic resin is selected from one or more of polybutadiene, polystyrene butadiene copolymer, polyphenylene ether, cycloolefin copolymer, SI and SIS copolymer, ethylene propylene diene copolymer, polyphenylene ether modified polystyrene butadiene rubber, polyphenylene ether modified SI and SIS copolymer.

[0034] Preferably, the first solvent can be selected from one or more non-polar solvents, such as toluene, xylene, etc.; the second solvent can be selected from one or more water, methanol, and ethanol solvents.

[0035] Preferably, the average particle size of the filler is 0.3-20 μm.

[0036] In a fourth aspect, the present invention provides use of the above filler in preparing semiconductor packaging materials or substrate materials.

[0037] Compared with the prior art, the present invention has the following technical effects: The filler with a multilayer structure of the present invention has a specific gravity suitable for the resin composition by adjusting the proportion of each structure of the hollow part, the low dielectric constant material layer, and the resin layer, so that the filler has excellent dispersibility in the resin composition, thereby playing a role in the low dielectric properties of the prepared substrate. Further, the present invention can make the filler have a low dielectric constant in a wide distribution range of 0.3 to 20 μm, thereby making fillers of different particle sizes play a grading role, so that the dielectric properties of the prepared substrate are further reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram of the structure of a filler with a multilayer structure according to the present invention, wherein: the figure marks are: 1. hollow part, 2. low dielectric constant material layer, 3. resin layer.

[0039] Figure 2 This is a photo of a finished product of a filler with a multi-layer structure according to the present invention.

[0040] Figure 3 This is a transmission electron microscope image of a filler with a multilayer structure according to the present invention. DETAILED DESCRIPTION

[0041] The present invention provides a filler having a multilayer structure, such as Figure 1 As shown, the filler is a spherical particle, which includes a low dielectric constant material layer 2, a hollow portion 1 surrounded by the low dielectric constant material layer, and a resin layer 3 arranged on the outer surface of the low dielectric constant material layer; The space of the hollow part 1 contains vacuum or gas, and the gas is selected from one or more of air and inert gas; the vacuum can be a relative vacuum state formed by vacuuming operation; The specific gravity of the filler is 0.4-1.5 g / cm 3 .

[0042] The filler with a multilayer structure of the present invention has a specific gravity suitable for the resin composition of 0.4-1.5 g / cm by adjusting the proportion of each structure of the hollow part, the low dielectric constant material layer and the resin layer. 3 , so that the filler has excellent dispersibility in the resin combination, and then the low dielectric properties of the obtained substrate are played a role. The material of the commonly used filler in the semiconductor field can be used as the making material of the low dielectric constant material layer of the filler of the present invention, so as to further reduce the dielectric constant and dielectric loss of the commonly used filler, and then the dielectric loss of the obtained substrate is reduced. The material of the commonly used filler in the semiconductor field has the characteristics of low dielectric constant.

[0043] The filler of the present invention has a multilayer structure, which makes the prepared substrate have an extremely low dielectric constant. The important thing is to adjust the proportion of each structural layer of the hollow part, the low dielectric constant material layer, and the resin layer. Therefore, the substrate is prepared under the same preparation conditions, and the filler is a filler with a multilayer structure of a hollow part, a low dielectric constant material layer, and a resin layer. If the specific gravity of the filler is 0.4-1.5g / cm 3 The dielectric constant of the substrate made of this filler is low. Although the dielectric constant of the air, vacuum or inert gas in the hollow part is lower than that of the low dielectric constant material layer and the resin layer, the dielectric constant of the filler as a whole can be reduced by increasing the volume proportion of the hollow part. However, if the specific gravity of the filler is not between 0.4 and 1.5 g / cm 3 In the range of 0.4-1.5 g / cm2, the dielectric constant of the substrate made of the filler is 0.4-1.5 g / cm2 compared with the above-mentioned specific gravity. 3 The dielectric constant of the substrate made with filler is higher.

[0044] In addition, since the resin layer is disposed on the outer surface of the low dielectric constant material layer, it is possible to prevent the resin composition components from being mixed into the low dielectric constant material layer during the subsequent process of mixing the filler with the resin composition to prepare the substrate, thereby preventing the dielectric constant of the low dielectric constant material layer from increasing. Therefore, when the substrate is prepared under the same preparation conditions and the specific gravity of the filler is the same appropriate specific gravity, the dielectric constant of the filler provided with the resin layer is lower than that of the substrate prepared without the filler.

[0045] In addition, due to the setting of the hollow part, the volume ratio of the hollow part can be adjusted as large as possible to take advantage of the low dielectric constant of air, vacuum or inert gas, and the overall specific gravity of the filler with a multilayer structure is 0.4~1.5g / cm 3The range of the dielectric constant of the substrate made of the filler is finally further reduced. The space of the hollow part contains vacuum, air or inert gas, which can be achieved by existing technology. For example, the hollow particles are directly prepared from the material forming the low dielectric constant material layer, and the hollow part and the low dielectric constant material layer can be directly integrated to form an inert gas. By further purging with inert gas, the space of the hollow part can contain inert gas.

[0046] Preferably, the specific gravity of the filler is 0.6-1.3 g / cm2 as measured by a true density meter based on an oxygen-based dry pycnometer. 3 .

[0047] Preferably, the volume of the hollow portion accounts for 33% to 95% of the total volume of the hollow portion and the low dielectric constant material layer.

[0048] The material forming the low dielectric constant material layer is often higher in dielectric constant than the resin layer material. However, the thermal expansion coefficient of the resin layer material is greater than that of the material forming the low dielectric constant material layer. When processing and preparing the substrate, there is an expansion difference. When the expansion difference is too large, there is a problem of peeling between the resin layer and the low dielectric constant material layer. The peeling of the resin layer will cause uneven dispersion of the filler and water absorption problems. Therefore, it is necessary to make the proportion of the resin layer smaller to reduce the expansion difference and avoid peeling of the resin layer. Therefore, in the filler of the present invention, on the premise of ensuring that the mass proportion of the resin material is reduced, the specific gravity of the filler is set at 0.4~1.5g / cm 3 , the dielectric constant of the filler can be made better (smaller). In the filler of the present invention, in order to reduce the amount of resin material used, the volume of the hollow part accounts for 33% to 95% of the total volume of the hollow part and the low dielectric constant material layer, which can make the dielectric constant of the filler with a multilayer structure smaller.

[0049] More preferably, the volume of the hollow portion accounts for 42% to 87% of the total volume of the hollow portion and the low dielectric constant material layer.

[0050] Preferably, under the condition of 1 GHz, the Dk of the material forming the resin layer is ≤3.

[0051] A resin material with a low dielectric constant Dk can make the dielectric constant of the prepared filler low, which ultimately helps to reduce the dielectric loss of the prepared substrate.

[0052] Preferably, the thickness of the resin layer does not exceed 1 / 4 of the diameter of the filler.

[0053] More preferably, the thickness of the resin layer does not exceed 300 nm.

[0054] Preferably, the average particle size of the filler is 0.3-20 μm.

[0055] Furthermore, the present invention can make the filler particle size have a wide distribution range of 0.3-20 μm, and has fillers with low dielectric constants within the wide particle size distribution range, giving play to the grading effect of fillers with different particle sizes, so that the dielectric loss of the prepared substrate is further reduced.

[0056] Preferably, between -60°C and 300°C, the thermal expansion coefficient of the material forming the low dielectric constant material layer is ≤20ppm / K.

[0057] By making the thermal expansion coefficient of the material forming the low dielectric constant material layer not exceed 20 ppm / K, the stability of the substrate can be improved, and the dielectric constant of the substrate can also be maintained at a low state after being placed for a period of time.

[0058] The present invention is further described below in conjunction with specific embodiments. In addition, the embodiments of the present invention involved in the following description are usually only embodiments of a part of the present invention, rather than all embodiments.

[0059] In the present invention, the test method of specific gravity is the true density instrument method, specifically: in an oxygen atmosphere, the specific gravity of the sample particles is obtained using the JW-M100A true density instrument produced by Beijing Jingwei Gaobo Science and Technology Co., Ltd.

[0060] Example 1 20g of polyphenylene ether (vinyl-terminated polyphenylene ether (SABIC, SA9000)) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50 = 0.49μm, hollow ratio of 68%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.93 g / cm 3 The thickness of the polyphenylene ether layer was 54 nm as measured by TEM, which accounted for 9.03% of the particle size of the filler. Figure 1 As shown in FIG. 1 , it is a photo of the finished product of the filler particles with a multilayer structure prepared in this embodiment; Figure 2 , which is a transmission electron microscope image of the filler particles prepared in this example, shows that the filler particles have a multilayer structure.

[0061] Example 2 20g of polybutadiene (epoxy-polybutadiene resin, crayvalley: Ricon184SB7, number average molecular weight of 9300g / mol) was completely dissolved in 200mL of toluene to obtain a polybutadiene solution. 2g of hollow silica particles (D50=0.34μm, hollow ratio of 80%, purchased from AGC Co., Ltd.) were added to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polybutadiene solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polybutadiene is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polybutadiene will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.60g / cm 3 , the thickness of the polybutadiene layer was found to be 85 nm through TEM test, which accounted for 16.67% of the particle size of the filler.

[0062] Example 3 20g of polybutadiene (polybutadiene resin, crayvalley: Ricon 100) was completely dissolved in 200mL of toluene to obtain a polybutadiene solution. 2g of hollow silica particles (D50=0.36μm, hollow ratio of 83%, purchased from AGC Co., Ltd.) were added to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polybutadiene solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polybutadiene is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polybutadiene will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.64 g / cm 3 , the thickness of the polybutadiene styrene layer was found to be 120 nm through TEM test, which accounted for 20.00% of the particle size of the filler.

[0063] Example 4 20g of cycloolefin copolymer (dicyclopentadiene epoxy resin ADEKA: EP-4088S) was completely dissolved in 200mL of toluene to obtain a cycloolefin copolymer solution. 2g of hollow silica particles (D50=0.44μm, hollow ratio of 65%, purchased from AGC Co., Ltd.) were added to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The cycloolefin copolymer solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since the cycloolefin copolymer is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated cycloolefin copolymer will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.89 g / cm 3 , the thickness of the cycloolefin copolymer layer was found to be 49 nm by TEM test, which accounted for 9.11% of the particle size of the filler.

[0064] Example 5 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.44 μm, hollow ratio of 65%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.84 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 49 nm through TEM test, which accounted for 9.11% of the particle size of the filler.

[0065] Example 6 40g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.41μm, hollow ratio of 60%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.00 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 102 nm through TEM test, which accounted for 16.61% of the particle size of the filler.

[0066] Example 7 40g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.42μm, hollow ratio of 42%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.30 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 105 nm through TEM test, which accounted for 16.67% of the particle size of the filler.

[0067] Example 8 Completely dissolve 40g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) in 200mL of toluene to obtain a polyphenylene ether solution. Add 2g of hollow silica particles (D50=0.40μm, hollow ratio of 37%, AGC Co., Ltd.) to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stir and disperse to obtain a template solution. Mix the polyphenylene ether solution with the template solution, stir and disperse to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate is centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.41 g / cm 3 The thickness of the polyphenylene ether layer was found to be 105 nm by TEM method, which accounted for 17.21% of the particle size of the filler.

[0068] Example 9 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.30 μm, hollow ratio of 71%, AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.73 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 33 nm through TEM test, which accounted for 9.02% of the particle size of the filler.

[0069] Example 10 40g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.73 μm, hollow ratio of 75%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.82 g / cm 3 The thickness of the polyphenylene ether layer was found to be 108 nm by TEM method, which accounted for 11.42% of the particle size of the filler.

[0070] Embodiment 11 Completely dissolve 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) in 200 mL of toluene to obtain a polyphenylene ether solution. Add 2g of hollow ceramic particles (D50=2μm, hollow ratio of 52%) to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stir and disperse, and obtain a template solution. Mix the polyphenylene ether solution with the template solution, stir and disperse to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate is centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.22 g / cm 3 The thickness of the polyphenylene ether layer was measured by TEM method and found to be 222 nm, which accounted for 9.08% of the particle size of the filler.

[0071] Example 12 Completely dissolve 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) in 200 mL of toluene to obtain a polyphenylene ether solution. Add 2g of hollow glass particles (hollow alumina borosilicate glass particles (MG-005 manufactured by Pacific Cement Company, D50=1.6μm, hollow ratio 80%)) to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stir and disperse to obtain a template solution. Mix the polyphenylene ether solution with the template solution, stir and disperse to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate is centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.55 g / cm 3 The thickness of the polyphenylene ether layer was found to be 178 nm by TEM method, which accounts for 9.10% of the particle size of the filler.

[0072] Comparative Example 1 A filler with a multilayer structure is provided, which is different from Example 1 in that: its specific gravity is 0.34 g / cm 3 . Prepare according to the following steps: 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.49 μm, hollow ratio of 85%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.34 g / cm 3 The thickness of the polyphenylene ether layer was found to be 53 nm by TEM test.

[0073] Comparative Example 2 A filler with a multilayer structure is provided. Compared with Example 1, the difference is that the hollow ratio of the hollow silica particles is 96%, and the specific gravity of the prepared filler is 0.26 g / cm 3 . Prepare according to the following steps: 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.49 μm, hollow ratio of 96%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 0.26 g / cm 3 The thickness of the polyphenylene ether layer was found to be 106 nm by TEM method.

[0074] Comparative Example 3 A filler with a multilayer structure is provided, which is different from Example 1 in that: its specific gravity is 1.62 g / cm 3 . Prepare according to the following steps: 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.49μm, hollow ratio of 34%, purchased from AGC Co., Ltd.) were added to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2.5 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.62 g / cm 3 The thickness of the polyphenylene ether layer was found to be 63 nm by TEM method.

[0075] Comparative Example 4 A filler with a multilayer structure is provided, which is different from Example 1 in that: its specific gravity is 1.79 g / cm 3 . Prepare according to the following steps: 20g of polyphenylene ether (vinyl-terminated polyphenylene ether SABIC: SA9000) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.49μm, hollow ratio of 16%, purchased from AGC Co., Ltd.) were added to 500mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 2 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.79 g / cm 3 The thickness of the polyphenylene ether layer was found to be 52 nm by TEM method.

[0076] Comparative Example 5 A filler with a multilayer structure is provided, which is different from Example 1 in that the thickness of the polyphenylene ether layer is greater than 1 / 4 of the diameter of the prepared filler. The filler is prepared according to the following steps: 50g of polyphenylene ether (vinyl-terminated polyphenylene ether (SABIC, SA9000)) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50=0.49μm, hollow ratio of 87%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 3 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.27 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 250 nm through TEM test, which accounted for 27.78% of the particle size of the filler.

[0077] Comparative Example 6 A filler with a multilayer structure is provided, which is different from Example 1 in that: the specific gravity of the filler is 1.60 g / cm 3 , the thickness of the polyphenylene ether layer is greater than 1 / 4 of the diameter of the prepared filler. Prepared according to the following steps: 50g of polyphenylene ether (vinyl-terminated polyphenylene ether (SABIC, SA9000)) was completely dissolved in 200 mL of toluene to obtain a polyphenylene ether solution. 2g of hollow silica particles (D50 = 0.49μm, hollow ratio of 57%, purchased from AGC Co., Ltd.) were added to 500 mL of an aqueous solution of sodium dodecyl sulfate surfactant with a mass concentration of 0.15%, stirred and dispersed to obtain a template solution. The polyphenylene ether solution was mixed with the template solution, stirred and dispersed to form a water-in-oil system. Since polyphenylene ether is insoluble in water, as the stirring proceeds and the toluene solvent gradually evaporates, the precipitated polyphenylene ether will be deposited on the surface of the hollow silica particles. After stirring for 3.5 hours, the precipitate was centrifuged and vacuum dried at 120°C for 4 hours to obtain a filler particle with a multilayer structure. After testing, the specific gravity of the filler particle is 1.60 g / cm 3 , the thickness of the polyphenylene ether layer was found to be 249 nm through TEM test, which accounted for 25.20% of the particle size of the filler.

[0078] Performance Characterization The fillers obtained in the embodiments and comparative examples were used to prepare substrates, and the dielectric constants were tested. The results are shown in Table 1. The initial dielectric constant is the dielectric constant tested on the first day after the substrate was prepared, and the placement dielectric constant is the dielectric constant tested 30 days after the substrate was prepared, which shows the stability of the dielectric constant of the substrate. The temperature and humidity of the placement environment are: 25°C, 70%RH.

[0079] The method for preparing the substrate is as follows: 10 parts by weight of filler powder, 50 parts by weight of liquid polyphenylene ether SA9000, 50 parts by weight of divinylbenzene oligomer resin, and 2.5 parts by weight of initiator diisopropylbenzene peroxide are weighed and mixed, and then 50 parts by weight of toluene are added, and the mixture is stirred and mixed evenly to obtain a glue solution. The above glue solution is impregnated with PTFE woven cloth, and a semi-cured sheet is obtained after drying to remove the solvent to form a prepreg; eight prepregs of the prepared semi-cured sheets are overlapped, and 1 oz thick copper foil is pressed on both sides thereof, and the substrate is cured in a press for 2 hours, wherein the curing pressure is 50 Kg / cm 2 The curing temperature is 230°C. The SPDR (splite post dielectric resonator) method is used to detect the dielectric constant of the substrate in accordance with the IPC4101 standard. The test conditions are A state, 10GHz, and the test instrument is a high-frequency vector network analyzer.

[0080] In Table 1, the graded filler is obtained by mixing the fillers of Example 9, Example 10 and Example 11 at a weight ratio of 1:2:7. The D50 of the hollow silica is 0.40 μm, and the hollow ratio is 37%.

[0081] Table 1 Filling Group Particle size (μm) <![CDATA[Specific gravity (g / cm 3 ).]]> Resin layer thickness (nm) Initial Dk Place Dk Example 1 0.49 0.93 54 2.50 2.51 Example 2 0.34 0.60 85 2.65 2.67 Example 3 0.36 0.64 120 2.60 2.62 Example 4 0.44 0.89 49 2.37 2.39 Example 5 0.44 0.84 49 2.57 2.58 Example 6 0.41 1.00 102 2.53 2.54 Example 7 0.42 1.30 105 2.60 2.62 Example 8 0.40 1.41 105 2.81 2.83 Example 9 0.33 0.73 33 2.34 2.36 Example 10 0.73 0.82 108 2.20 2.22 Embodiment 11 2.0 1.22 222 2.59 2.61 Example 12 1.6 0.55 178 2.65 2.67 Graded filler / / / 2.40 2.40 Comparative Example 1 0.49 0.34 53 3.13 3.18 Comparative Example 2 0.49 0.26 106 3.23 3.30 Comparative Example 3 0.49 1.62 63 3.17 3.24 Comparative Example 4 0.49 1.79 52 3.23 3.44 Comparative Example 5 0.49 1.27 250 3.21 3.27 Comparative Example 6 0.49 1.60 249 3.30 3.37 <![CDATA[Hollow SiO2]]> 0.49 0.72 0 2.90 2.94 From Table 1, we can see that: (1) The filler with a multilayer structure of the present invention has a specific gravity suitable for the resin composition by adjusting the proportion of each structure of the hollow part, the low dielectric constant material layer, and the resin layer, so that the filler has excellent dispersibility in the resin composition, so that the low dielectric properties of the substrate prepared with the filler can be exerted. Furthermore, the present invention can make the filler have a low dielectric constant in a wide distribution range of 0.3~20μm, and then make the fillers of different particle sizes play a grading role, so that the dielectric properties of the prepared substrate are further reduced, as shown in the characterization data of the graded filler.

[0082] (2) The theoretical dielectric constant of the substrate obtained by using graded fillers is: initial Dk = 2.487 (2.34*1 / 10+2.20*2 / 10+2.59*7 / 10); placed Dk = 2.507 (2.36*1 / 10+2.22*2 / 10+2.61*7 / 10). By comparing the graded fillers with Examples 9, 10, and 11, it can be seen that compared with the theoretical dielectric constant of the fillers obtained by using different filler grading combinations, the dielectric constant of the substrate obtained by using the grading of fillers with different particle sizes in the present invention is further reduced. At the same time, the Dk stability of the substrate is better. The reason is that the use of graded fillers with different particle sizes can increase the filling rate, increase the overall hollowness of the substrate after filling, and thus reduce the dielectric constant of the substrate. The fillers of the present invention have a specific gravity of 0.4~1.5g / cm 3 The filler used in the gradation can be filled more evenly, which is beneficial to improve the filling rate of the substrate. Therefore, the dielectric constant of the substrate prepared by the present invention is lower than the theoretical value. The substrate prepared by the graded filling filler is not easy to crack. The filler provided by the present invention has the characteristics of low dielectric constant in a wide particle size range of 0.3 to 20 μm, which has great advantages in gradation application.

[0083] (3) By comparing comparative examples 1 and 3 with example 1, it can be seen that by adjusting the proportions of the hollow part, the low dielectric constant material layer, and the resin layer, the specific gravity is adjusted to be suitable for the resin composition, and the preferred specific gravity range is 0.4 to 1.5 g / m 3 If the specific gravity is not within this range, as shown in the data of Comparative Examples 1 and 3, the dielectric constant will increase and the placement stability will deteriorate.

[0084] (4) From the comparative analysis of Comparative Examples 1 to 4 and Example 1, it can be seen that in order to reduce the dielectric constant of the substrate, the specific gravity of the filler needs to be controlled within 0.4-1.5 g / m 3 At the same time, as shown in Comparative Examples 2 and 4, if the volume ratio of the hollow portion (hollowness ratio) is not within the range, its placement stability becomes poor.

[0085] (5) From the comparative analysis of Comparative Examples 5 and 6 with Example 1, it can be seen that if the thickness of the resin layer exceeds 1 / 4 of the diameter of the entire filler, the dielectric constant of the substrate obtained will be greatly increased, and the placement stability will be poor. The reasons are analyzed as follows: First, if the thickness of the resin layer is too thick, there will be more gaps between the silicon dioxide layer and the surface resin layer, and the resin layer is easy to peel off, which will increase the water absorption of the final substrate; secondly, the density of the resin layer material is lower than that of silicon dioxide. If the resin layer is too thick, the obtained filler will float, resulting in uneven distribution of the substrate material. This unevenness will cause the substrate to absorb water, which will lead to an increase in the dielectric constant; thirdly, the dielectric constant of the resin layer material is higher than that of silicon dioxide. If the resin layer is too thick, the dielectric constant of the obtained filler will increase; therefore, in summary, the dielectric constant of the substrate finally prepared increases.

[0086] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A filler with a multilayer structure, characterized in that: The filler is a spherical particle, which comprises a low dielectric constant material layer (2), a hollow portion (1) formed by the low dielectric constant material layer, and a resin layer (3) arranged on the outer surface of the low dielectric constant material layer; The space of the hollow part contains vacuum or gas, and the gas is selected from one or more of air and inert gas; The specific gravity of the filler is 0.4-1.5 g / cm 3 .

2. A filler with a multilayer structure as claimed in claim 1, characterized in that: The specific gravity of the filler is 0.6-1.3 g / cm 3 .

3. A filler with a multilayer structure as claimed in claim 1, characterized in that: The volume of the hollow portion accounts for 33% to 95% of the total volume of the hollow portion and the low dielectric constant material layer.

4. A filler with a multilayer structure as claimed in claim 3, characterized in that: The volume of the hollow portion accounts for 42% to 87% of the total volume of the hollow portion and the low dielectric constant material layer.

5. The filler with a multilayer structure as claimed in claim 1, characterized in that: Under a condition of 1 GHz, the Dk of the material forming the resin layer is ≤3.

6. A filler with a multilayer structure as claimed in claim 1 or 4, characterized in that: The thickness of the resin layer does not exceed 1 / 4 of the diameter of the filler.

7. A filler with a multilayer structure as claimed in claim 1, characterized in that: The average particle size of the filler is 0.3-20 μm.

8. The filler with a multi-layer structure as claimed in claim 1, characterized in that: Between -60°C and 300°C, the thermal expansion coefficient of the material forming the low dielectric constant material layer is ≤20ppm / K.

9. A method for preparing a filler with a multilayer structure, characterized in that: The following steps are involved: Step S1: adding an organic resin into a first solvent to form a solution; Step S2: providing a hollow spherical particle, and dissolving the hollow spherical particle in a second solvent to form a dispersion; Step S3: mixing the dispersion with the solution to precipitate the organic resin and form a resin layer on the surface of the hollow spherical particles; Step S4: separating the solid and liquid of the mixed system obtained in step S3, and drying the solid to obtain a filler; The specific gravity of the filler is 0.4-1.5 g / cm2 as measured by a true density meter using a dry pycnometer based on oxygen. 3 .

10. The preparation method according to claim 9, characterized in that: The hollow ratio of the hollow spherical particles is 33-95%.

11. The preparation method according to claim 9, characterized in that: The thickness of the resin layer does not exceed 1 / 4 of the diameter of the filler.

12. The preparation method according to claim 9 or 11, characterized in that: The organic resin is selected from one or more of polybutadiene, polystyrene butadiene copolymer, polyphenylene ether, cycloolefin copolymer, SI and SIS copolymer, ethylene propylene diene copolymer, polyphenylene ether modified polystyrene butadiene rubber, polyphenylene ether modified SI and SIS copolymer.

13. The preparation method according to claim 9, characterized in that: The average particle size of the filler is 0.3-20 μm.

14. Use of the filler according to any one of claims 1 to 8, or the filler prepared by the preparation method according to any one of claims 9 to 13 in preparing semiconductor packaging materials or substrate materials.

Citation Information

Patent Citations

  • Hollow silica particles and method for producing same

    CN109071239A